Worker Remittances and Capital Flows - Claudia M. Buch; Anja Kuckulenz; Marie-Helene Le Manchec (Kiel Institute for World Economics (IfW), 2002)
The debate on the risks and benefits of the globalisation of international capital markets has focused on the volume and the volatility of the main capital flows – foreign direct investment (FDI), portfolio investment, and foreign bank lending. Financial transfers in the form of worker remittances have received less attention in this context. This paper provides an analysis on the magnitude of remittances, their volatility, and their relationship to other capital flows. Moreover, we provide empirical evidence on the determinants of remittances and private capital flows.
Keywords: J61; F36; F22; 330; remittances; migration; capital flows; Gastarbeiterüberweisung; Internationale Kapitalmobilität; Schätzung; Welt